(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2024)
Background. The design of new luminescent materials based on isotropic oxide glasses is one of the key tasks for optimizing the optical properties of modern LED lighting sources. Particularly noteworthy are glasses based on phosphate – borate system, which contain modifiers of optical properties. Among them, europium(III) oxide is responsible for luminescent properties, and molybdenum(VI) oxide is a partial glass-forming and sensitizing agent. Methods. In this work, a method of rapid cooling of a salt melt was used to obtain phosphate-borate glasses, followed by quenching of the obtained samples on a copper sheet. The glasses were characterized by infrared and luminescence spectroscopy, diffuse reflectance spectroscopy, and X-ray diffraction analysis. Results. The pecularities of obtaining phosphate-borate glass modified with molybdenum(VI) oxide of the following composition have been established: (45-0.5x)P2O5-xB2O3 -10.0MoO3 -(45-0. 5x)Na2O (x = 20.0-60.0) and it is shown that an increase in the concentration of B2O3 from 45 to 60 % mol is accompanied by an increase in the hygroscopicity of the obtained amorphous materials and a decrease in solubility relative to Eu2O3 at an isothermal holding of 1000 °C. For the first time, the influence of B2O3 on the structure of glasses is shown, namely, when x = 45 % mol B2O3 is reached, the density of glasses increases from ρ = 2.20 g/cm-1 to ρ = 2.45 - 2.50 g/cm-1, which is responsible for the formation of additional chains in glass due to the greater coordination capacity of borate tetrahedra compared to phosphate ones. Conclusions. It has been shown that the most promising for modeling red phosphors is the glass 34.95P2O5 - 20.0B2O3 -10.00MoO3 - 34.95Na2O - 0.1Eu2O3, which is effectively excited by UV radiation. The band gap for the resulting luminescent glass is estimated as 3.65 eV.